Karen's grandmothers ebook - Yingst, DK (Baby-Sitters Little Sister Graphix, 2024)
Another graphic novel in this fun series spin-off from The Baby-sitters Club, adapted by newcomer DK Yingst! When Karen adopts a grandmother from Stoneybrook Manor, she has more grandmas than anyone she knows — five! Karen thinks that is very special. But Karen's new grandmother is so different! Grandma B makes Karen listen to old music, and she teaches Karen funny dances, like the foxtrot. Are five grandmothers too many for Karen?